Identificación de patrones urbanos en el borde del Río Chibunga tramo delimitado por la Avenida Atahualpa y Félix Proaño - Guamán Muela, Milton Danilo (2019)
The growth of cities all around the world as becoming unavoidable. Studies show that when population increases, physical space mirrors, and does the same. This growth, unfortunately, has occurred in a disorderly manner in many cities around Latin America, including Riobamba, whose case is no exception. The population increase has created chaos in the relationship between the physical-inhabitants space and the different areas that make up the urban population. At the time of planning a city, or village, most often the urban pattern is not taken into consideration when it comes to the urban form of global study. This research seeks to identify urban trends, characterize and rank them. A famous case study occurred in the Riobamba city – Ecuador, which was designed explicitly by the Felix Proaño Avenue and Atahualpa Avenue. Who applied the visual methodology, proposed by Stephen Wheeler (2015) This is based on five elements which define a specific type of pattern. The results reveal the existence of 16 patterns in the urban area, and 9 in the area under study. This identification allows us to become aware of the advantages and disadvantages offered by each employer. And thus, propose planning recommendations that help one take advantage and improve their shortcomings. Eventually, this leaves options of possibility open to future research on this subject, allowing different fields to become familiar whit the options that urbanization has to offer.